Makna Hombo Batu bagi Masyarakat Desa Bawamataluo Nias Selatan - Martina Rosmaulina Marbun; Lena Juliani Halawa (Journal New Light, 2025)
Hombo Batu, or fahombo, is a Nias tradition involving jumping over tall rocks, now widely recognized as a cultural icon, particularly in Bawomataluo Village, South Nias. This research was conducted to examine the symbolic, historical, and contemporary relevance of this cultural practice in the lives of local communities. The method used was a descriptive qualitative approach combining literature review, participant observation, and the study of various relevant academic documents. The research findings indicate that Hombo Batu is not merely a test of physical strength or courage, but also a means of affirming cultural identity, strengthening social solidarity, and educating the younger generation about values ​​and character. The meaning has shifted over time, from its original function as a traditional military exercise to prepare young people to defend their villages, to its development as a cultural attraction and tourist attraction with economic value. These changes do not necessarily eliminate the traditional meaning, as Hombo Batu remains viewed as a symbol of dignity, honor, and cultural heritage that must be preserved. Therefore, this study emphasizes the importance of local community-based preservation, the implementation of adaptive conservation strategies so that traditions remain relevant to the modern context, and the integration of Hombo Batu into character education and sustainable tourism, so that this cultural heritage can continue to live and make a positive contribution to the Nias community and the nation at large.